Sie sind auf Seite 1von 2

FACULTY OF SCIENCE, ARTS AND HERITAGE

UNIVERSITI TUN HUSSEIN ONN MALAYSIA

BWM10203/ BSM 1923 TUTORIAL 4

Elementary functions and properties of inverse Laplace transforms

Find the inverse Laplace transform of following functions using table of Laplace trancform.
2 3s 2
(a) F (s) = 2 - 2 (Answer: f (t ) = sin 3t - 3cosh 2t )
s +9 s -4 3
5 1 5 2t 3
(b) F (s) = + 2 (Answer: f (t ) = e t + e t )
-2 t
( s - 2) 4
s + 4s + 4 6
-14 s -2 s
11 e 6e
(c) F (s) = - + (Answer: f (t ) = 11 - e9(t -14) H (t - 14) + 6 H (t - 2) )
s s+9 s
4
(d) F (s ) = 2 (Answer: f (t ) = sin 4t )
s + 16
6
(e) F (s) = (Answer: f (t ) = e -2t t 3 )
( s + 2) 4
2e -2 s 1 2t -4 1
(f) F (s ) = 2 (Answer: f (t ) = H (t - 2)e - H (t - 2)e -2t + 4 )
s -4 2 2
-s
( s - 2)e 1 t -1 1 3t - 3
(g) F (s) = 2 (Answer: f (t ) = H (t - 1)e + H (t - 1)e )
s - 4s + 3 2 2

Partial fraction and completing the square

Find the inverse Laplace transform of following functions.


s+2
(a) F (s) = 2 (Answer: f (t ) = e -2t cos 3t )
s + 4s + 7
2s + 7 -3t �2 1 �
(b) F (s) = 4 (Answer: f (t ) = e �t + t 3 �)
( s + 3) � 6 �
-4 s
3e - 4s �5 1 3(t -4) � 4
(c) F (s) = 2 (Answer: f (t ) = � - t + e �H (t - 4) + (1 - e ) )
3t

s ( s - 3) �3 3 � 3
s - 18
(d) F (s) = (Answer: f (t ) = 4e -2t - 3e3t )
( s + 2)( s - 3)
-2 s 3 - 8s 2 + 8s + 6
(e) F (s) = (Answer: f (t ) = 2t + 2e -3t - 4e -t )
( s + 3)( s + 1) s 2

Convolution theorem

Find the inverse Laplace transform of following functions using convolution.


7 7
(a) F (s) = (Answer: f (t ) = (1 - cos 6t ) )
s ( s + 36)
2
36
3 3 2 3
(b) F (s) = 3 3 (Answer: f (t ) = - t - 9t - 18 + t 2 et - 9tet + 18et )
s ( s - 1) 2 2

Prepared by : Pn Syahirbanun binti Isa


1 1 8t
1
t
(c) F ( s) = (Answer: f (t ) = (e - e 3 ) )
( s - 8)(3s - 1) 23

Application: Initial value problem and boundary value problem

1. Solve the following initial value problems.


(a) 4 y�� - 4 y� + 3 = -9, y (0) = -2, y � (0) = -1 (Answer: y (t ) = 2 - 4et )
(b) y�� + 6 y� = H (t - 8), y (0) = 0, y � (0) = 0
1 49 1
(Answer: y (t ) = tH (t - 8) - H (t - 8) + e -6t + 48 H (t - 8) )
6 36 36
(c) y �
� + y = g (t ); y (0) = 0, y �
(0) = 1
�t / 2, 0 �t < 6
g (t ) = �
�3, t �6
(Answer:)

(d) 2 y�
� + 2 y = d (t - 5) , y (0) = 0, y �
+ y� (0) = 0 (Answer:)
1
(e) y�
�- 2 y� (0) = 1 (Answer: y = -3et + 4tet + t 3 et + 4 )
+ y = tet + 4, y (0) = 1, y �
6

2. Solve the following boundary value problem


7 14
y�
� = 7 cos 3t , y (0) = 0, y (p ) = 5 (Answer: y (t ) = 0.009e 2t -
- 2 y� cos 3t - sin 3t + 0.529 )
13 39

Prepared by : Pn Syahirbanun binti Isa